2012
DOI: 10.1371/journal.pone.0034150
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of miRNAs in Colorectal Cancer: Comparison of Paired Tumor Tissue and Adjacent Normal Mucosa Using High-Throughput Sequencing

Abstract: We present the results of a global study of dysregulated miRNAs in paired samples of normal mucosa and tumor from eight patients with colorectal cancer. Although there is existing data of miRNA contribution to colorectal tumorigenesis, these studies are typically small to medium scale studies of cell lines or non-paired tumor samples. The present study is to our knowledge unique in two respects. Firstly, the normal and adjacent tumor tissue samples are paired, thus taking into account the baseline differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 60 publications
(81 reference statements)
6
116
0
1
Order By: Relevance
“…Our findings revealed that epigenetic silencing of miR-490-3p promoted gastric tumorigenesis by upregulating SMARCD1, a member of the SWItch/Sucrose NonFermentable (SWI/SNF) chromatin remodeling family involved in cancer development (18). MiR-490-3p has been shown to exert tumor-suppressing actions in other types of cancer, such as colon and lung cancers (19,20). Here, we demonstrated that promoter DNA hypermethylation of its host gene CHRM2 might account for the downregulation of miR-490-3p in gastric cancer.…”
Section: Discussionmentioning
confidence: 79%
“…Our findings revealed that epigenetic silencing of miR-490-3p promoted gastric tumorigenesis by upregulating SMARCD1, a member of the SWItch/Sucrose NonFermentable (SWI/SNF) chromatin remodeling family involved in cancer development (18). MiR-490-3p has been shown to exert tumor-suppressing actions in other types of cancer, such as colon and lung cancers (19,20). Here, we demonstrated that promoter DNA hypermethylation of its host gene CHRM2 might account for the downregulation of miR-490-3p in gastric cancer.…”
Section: Discussionmentioning
confidence: 79%
“…Accordingly, re-expression of miR-1 in bladder cancer (Yoshino et al 2011), hepatocellular carcinoma , lung cancer ) and rhabdomyosarcoma (Yan et al 2009) inhibits tumour cell growth and metastatic traits. Deep sequencing has also found miR-1 levels to be reduced in colorectal cancers (CRCs) and a case of colorectal NET (Hamfjord et al 2012). miR-1 downregulation in human CRCs has been correlated with over-expression of the MET gene, especially in advanced stages of progression (Migliore et al 2012).…”
Section: Global Mirna Profiling Reveals a Signature Specific For Smalmentioning
confidence: 99%
“…It has been suggested that this cluster is unregulated in colon cancer tissues. To confirm the expression levels of the members of this gene cluster in colon cancer, a total of five previous studies (Table I) (16)(17)(18)(19)(20), which investigated miRNA expression in colon cancer, were examined and the fold changes of these three miRNAs in colon cancer tissues were compared with those in normal tissue. The clinical characteristics of these studies were extracted and are listed in Table I.…”
Section: Resultsmentioning
confidence: 99%